Typhidot IgM as a reliable and rapid diagnostic test for typhoid fever among children in a tertiary care hospital - Ansari, Mohammad Ashfaque; Thakur, Amit Kumar; Mishra, Atindra; Rain, Md Jaffer (International Journal of Contemporary Pediatrics, 2020)
Background: Typhoid fever still continues to be a major public health problem in Nepal. A clinical spectrum of typhoid varies widely. It causes significant complication as well as mortality. A simple, reliable, affordable and rapid diagnostic test has been a long felt need of the clinicians to prescribe specific medication, adopt prevention of the emergence of antibiotics resistance and overall reduce the disease burden in the community. Methods: The prospective descriptive study was performed in 125 children between 2 years to 15 years of age admitted to the Pediatrics Department from September 2017 to September 2018. Blood culture, Typhidot rapid IgM were performed. MEDCALC software was used to calculate 95% confidence interval for sensitivity, specificity, predictive value positive, predictive value negative and accuracy. Kappa test was used to determine the agreement between Typhidot IgM and blood culture methods. Results: The study consisted of 125 children with acute febrile illness for more than 3 days with clinical symptomatology, consistent with typhoid fever. The reliability of Typhidot IgM in relation with blood culture and the study lighten that sensitivity 92.3% (95% CI: 63.9, 99.8), specificity 49.1% (95% CI: 39.5, 58.7), PPV 17.4% (95% CI: 14.2, 21.1), NPV 98.2% (95% CI: 89.2, 99.7) and accuracy 53.6% (95% CI: 44.5, 62.6). The two methods i.e. Typhoid IgM and blood culture shows significant agreement with p value 0.004. Conclusions: The present study demonstrates that Typhidot IgM has all the attributes of an ideal screening test.